Analisis Perbaikan dan Pemeliharaan Sistem Pendingin (Air Conditioner) Pada Mobil Jazz New - Gowasa, Estomi; Afdal, Afdal; Selviyanty, Veny; Abu, Risal; Mukhnizar, Mukhnizar (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
In a new Honda Jazz car, there is a rotten smell coming from inside the AC cabin, the temperature is not cold and causes the windshield to fog up. The purpose of the research is to find out the causes of damage to the AC system and appropriate maintenance actions. The method used is primary data, namely by direct inspection it is known that the refrigerant parameters are low on the pressure gauge manifold device on both sides LO 0.6–0.8 kg/cm2 and HI 8–9 kg/cm2. Damage to the capillary pipe is leaking. The action taken is to replace the capillary tube components, so the temperature parameters become LO=1.5–2.0 kg/cm² and HI=14.5–15 kg/cm². Once the pressure on the compressor, LO=4–6 kg/cm² and LO=7–10 kg/cm². The temperature is hot in the vehicle cabin. After replacing the compressor Normal pressure LO=1.5–2.0 kg/cm² and HI=14.5–15 kg/cm². Unstable Condenser temperature, LO=15Psi. HI=300–350Psi. cleaning is carried out at the temperature parameters LO=25Psi and HI=150 Psi, normal conditions. The hot room temperature = 29.2ºC and the cleaning action is carried out, then the temperature becomes = 16.8ºC, the AC room temperature returns to normal.